The effect of alcohol on ionizing and non-ionizing drug release from hydrophilic, lipophilic and dual matrix tablets - Václav Lochař; Alena Komersová; Kevin Matzick; Barbora Slezáková; Martin Bartoš; Jitka Mužíková; Samir Haddouchi (Elsevier, 2020)
The aim of this work was to investigate and quantitatively evaluate the effect of presence of alcohol on in vitro release of ionizing and non-ionizing drug from hydrophilic, lipophilic and hydrophilic-lipophilic matrix tablets. The Food and Drug Administration (FDA) recommends in vitro dissolution testing of extended release formulations in ethanolic media up to 40% because of possible alcohol-induced dose dumping effect. This study is focused on comparison of the dissolution behavior of matrix tablets (based on hypromellose and/or glyceryl behenate as retarding agent) of the same composition containing different type of drug - ionizing tramadol hydrochloride (TH) and non-ionizing pentoxifylline (PTX). The dissolution tests were performed in acidic medium (pH 1.2) and in alcoholic medim (20%, 40% of ethanol) and the changes of tablets were observed also photographically.It was found that the alcohol resistence of the hydrophilic-lipophilic formulations with TH and the hydrophilic-lipophilic formulations with PTX containing a higher amount of hypromellose does not reflect the alcohol resistence of the formulations with pure hypromellose or glyceryl behenate. Both hydrophilic-lipophilic formulation with TH and more lipophilic formulation with PTX show significant alcohol dose dumping effect. Keywords: Hypromellose, Glyceryl behenate, Alcohol, Tramadol hydrochloride, Pentoxifylline, Dissolution